Validation of a proxy‐reported SARC‐F questionnaire for current and retrospective screening of sarcopenia‐related functional impairments. Issue 1 (12th December 2021) - Maurus, Johannes; Terzer, Tobias; Benner, Axel; Goisser, Sabine; Eidam, Annette; Roth, Anja; Janssen, Maike; Jaramillo, Sonia; Lorenz, Hannes Martin; Micol, William; Hauer, Klaus; Müller‐Tidow, Carsten; et al.
Abstract: Background: The strength, assistance walking, rise from a chair, climb stairs, and falls (SARC‐F) questionnaire is a well‐established instrument for screening of sarcopenia and sarcopenia‐related functional impairments. As it is based on self‐reporting, its use precludes patients who are unable to answer the questionnaire as a consequence of severe acute diseases or cognitive impairment. Therefore, we aimed to validate a proxy‐reported version of the SARC‐F for both ad‐hoc as well as retrospective screening for severe sarcopenia‐related functional impairments. Methods: Patients aged ≥60 years completed the SARC‐F and performed the short physical performance battery (SPPB) at baseline (T1). Proxies in Cohort A gave a simultaneous assessment of the patients' functional status with the proxy‐reported SARC‐F at T1 and again, retrospectively, after 3 months (T2). Proxies in Cohort B only completed the SARC‐F retrospectively at T2. The questionnaires' performances were assessed through sensitivity/specificity analyses and receiver operating characteristic (ROC) curves. For non‐inferiority analyses, results of both the patient‐reported and proxy‐reported SARC‐F were correlated with the SPPB total score as well as the results of the chair‐rise test subcategory; the respective correlation coefficients were tested against each other. Results: One hundred and four patients and 135 proxies participated. Using a SPPB score < 9 points as the reference standard, the proxy‐reported SARC‐F identified patients at high risk for sarcopenia‐related functional impairment with a sensitivity of 0.81 (ad‐hoc), 0.88 (retrospective Cohort A), and 0.87 (retrospective Cohort B) as well as a specificity of 0.89 (ad‐hoc), 0.78 (retrospective Cohort A), and 0.64 (retrospective Cohort B). Areas under the ROC curves were ≥ 0.9 for the ad‐hoc proxy‐reported SARC‐F and the retrospective proxy‐reported SARC‐F in both cohorts. The proxy‐reported SARC‐F showed a non‐inferior correlation with the SPPB compared with the patient‐reported SARC‐F for ad‐hoc ( P  = <0.001) as well as retrospective screening for severe sarcopenia‐related functional impairment in both Cohorts A ( P  = 0.007) and B ( P  = 0.026). Conclusions: Proxy‐reported SARC‐F is a valid instrument for both ad‐hoc as well as retrospective screening for sarcopenia‐related functional impairment and could become the standard tool for evaluating this risk in older adults with severe acute disease, for example, in patients with quickly evolving haematological conditions.